1981
DOI: 10.1128/aem.42.4.672-676.1981
|View full text |Cite
|
Sign up to set email alerts
|

Immobilization of Escherichia coli Cells Containing Aspartase Activity with Polyurethane and Its Application for l -Aspartic Acid Production

Abstract: Whole cells of Escherichia coli containing aspartase activity were immobilized by mixing a cell suspension with a liquid isocyanate-capped polyurethane prepolymer (Hypol). The immobilized cell preparation was used to convert ammonium fumarate to L-aspartic acid. Properties of the immobilized E. coli cells containing aspartase were investigated with a batch reactor. A 1.67-fold increase in the L-aspartic acid production rate was observed at 37°C as compared to 25°C operating temperature. The pH optimum was broa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1984
1984
2017
2017

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 48 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Some researchers have assumed that covalent bonds are formed between the polyurethane polymer and the cell surface during immobilization (8). Electron microscopy of Escherichia coli immobilized in polyurethane suggested that the cells were attached to the solid structure of the matrix (10).…”
Section: Mineralization Of Pcp To Co2 By Polyurethane-entrappedmentioning
confidence: 99%
“…Some researchers have assumed that covalent bonds are formed between the polyurethane polymer and the cell surface during immobilization (8). Electron microscopy of Escherichia coli immobilized in polyurethane suggested that the cells were attached to the solid structure of the matrix (10).…”
Section: Mineralization Of Pcp To Co2 By Polyurethane-entrappedmentioning
confidence: 99%
“…As a result, L-aspartic acid production on an industrial scale using Escherichia coli cells immobilized in polyacrylamide was developed in 1973 (Chibata et al, 1974). Subsequently, various other polymers for this process have been proposed and applied (Chibata et al, 1985, Fusee et al,1981; however, it is obvious that continuous improvement of both the biological agents and process technology is necessary. We have previously described our investigations on strain improvement (Gadomska et al, 2007;Papierz et al, 2007) and in this paper, we present our own immobilization method of whole E. coli cells in chitosan for L-aspartic acid biosynthesis in continuous process in column bioreactors.…”
Section: Introductionmentioning
confidence: 99%
“…It indeed offers a simple and practicable method for enzyme immobilization and has potential for practical applications in various bioreactors. mers, [9][10][11][12]16,22,23,26,30…”
Section: Introductionmentioning
confidence: 99%